Enhancing MSME: Exploring the Relationship between Financial Literacy, Financial Inclusion, and Capital Access to Improve Performance - Naelati Tubastuvi; Rania Nur Ainun; Wida Purwidianti; Luthfi Zamakhsyari (Airlangga Journal of Innovation Management, 2024)
The growth of micro, small, and medium-sized enterprises (MSMEs) is critical to Indonesia's present economic development. This study has the purpose of examining how financial literacy, financial inclusion, and access to capital affect the performance of MSMEs in the Banyumas area. The performance of MSMEs is the dependent variable in this study, and the independent factors are financial literacy, financial inclusion, and access to finance. This study used partial Least Squares (PLS) to handle data in this work. Purposive sampling procedures were employed to select 127 MSMEs from a total of 8,559 MSMEs in the Banyumas Regency as research participants. The study's main findings of the relationship between the three variables of financial literacy, financial inclusion, and access to capital on MSME performance show that these three variables significantly influence MSME performance, both partially and simultaneously. As a result, MSMEs with a high degree of financial competence, simple access to finance, and suitable access to capital would improve MSMEs' performance in an area, resulting in the growth of the enterprises they manage. This research found that the financial literacy level of Banyumas MSMEs is quite high, available financial inclusion is easily accessible and sufficient access to capital can help MSMEs to improve their performance so that they can increase the development of the businesses they run.